Heart evoked potential triggers brain responses to natural affective scenes: A preliminary study - Couto, Juan Blas Marcos (2015)
The relationship between ongoing brain interoceptive signals and emotional processes has been addressed only indirectly through external stimulus-locked measures. In this study, an internal body trigger (heart evoked potential, HEP) was used to measure ongoing internally triggered signals during emotional states. We employed high-density electroencephalography (hd-EEG), source reconstruction analysis, and behavioral measures to assess healthy participants watching emotion-inducing video-clips (positive, negative, and neutral emotions). Results showed emotional modulation of the HEP at specific source-space nodes of the fronto-insulo-temporal networks related to affective-cognitive integration. This study is the first to assess the direct convergence among continuous triggers of viscerosensory cortical markers and emotion through dynamic stimuli presentation.